AI-11 The kinase inhibitory region of suppressor of cytokine signaling-1 modulates autoinflammatory skin pathology. (August 2018) - Veal, Antia E; Lam, Brandon; Collins, Teresa; Larkin, Joseph
Abstract : Background: Although aberrant antibody production is a lupus disease hallmark, abundant evidence implicates a dysregulated peripheral T lymphocyte repertoire in the onset and progression of lupus. Notably, the intracellular protein suppressor of cytokine signaling-1 (SOCS1) has been shown to regulate T lymphocyte effector functions and modulate lupus-like pathologies in rodent models. Significantly, peritoneal injection of a peptide (SOCS1-KIR), capable of mimicking SOCS1, was effective in mitigating T lymphocyte effector functions associated with lupus disease progression. Moreover, topical application of SOCS1-KIR 'eyedrops' was effective in mitigating experimental autoimmune uveitis. The peptide has been shown to function through the inhibition of the janus kinases Jak2 and Tyk2. We have previously shown that peritoneal injection of SOCS1-KIR inhibited lymphadenopathy in MRL lpr/lpr mouse model of spontaneous lupus that was correlated to decreased frequencies of interferon gamma producing memory T cells (Collins et al, 2018 (under revision)). In addition, the peritoneal injection of SOCS1-KIR also inhibited spontaneous lesion formation=In this study we test the hypotheses that SOCS1 modulates skin pathology and that topical application of the SOCS1-KIR peptide will have efficacy in the imiquimod induced lesion model. Methods: SOCS1 heterozygous mating pairs, sufficient and deficient of interferon gamma, were obtained from St. Jude and used to generate mice used in the experiment. Spontaneous skin lesions were assessed by histology. In addition, cytokine neutralizing antibodies were administered to evaluate mechanisms promoting lesion formation. Imiquimod was administered in the presence or absence of SOCS1-KIR to mice sufficient and deficient in SOCS1. Lesion formation was subsequently assessed. Results: SOCS1 ± IFN gamma -/- mice, but not SOCS ±, or IFN gamma -/- spontaneously developed epidermal hyperplasia. The SOCS1 ±, IFN gamma skin lesions were heavily infiltrated with macrophages and IL17 producing T lymphocytes. In addition, imiquimod induced skin lesions were exacerbated on SOCS1 ± mice compared to WT. Significantly, the topical administration of SOCS1-KIR to imiquimod treated murine skin reduced epidermal hyperplasia, erythema, and scaling. Conclusions: Together these results suggest that a peptide mimic of SOCS1 may have value as a therapeutic for lupus through topical and/or systemic administration. Acknowledgements: The study was supported by a grant from the Lupus Research Institute, The national Psoriasis Foundation, a BD Biosciences Research Grant, the NIH/NCATS Clinical and Translational Science Awards to the University of Florida TL1 TR000066 and UL1TR000064, a sub-award from NIH/NIAID/U01AI101990, and the University of Florida.